Changes to the Editorial Team of the IJSM - Duarte, José Alberto Ramos (International Journal of Sports Medicine, 2018)
There have been some changes to the Board of Editors of the IJSM. Already this year, Prof. Donald Dengel of the University of Minnesota, USA, replaced editor Prof. Joseph Houmard, who had been with the journal since 2006 and chose to leave the team for professional reasons.Unfortunately, our Editor-in-Chief Prof. Appell Coriolano is fast approaching his retirement from academia and will also be leaving the IJSM editorial team. Hans-Joachim Appell Coriolano joined the Editorial Board of the IJSM in 1987 and accepted the position of Assistant Editor in 1989. Over the years, he gradually assumed even greater responsibility for manuscript organization and editing. He has served as Editor-in-Chief since 2006 and is regarded as a true “primus inter pares” within the editors' team. For his tremendous commitment and unwavering dedication to the IJSM for nearly 30 years, Prof. Appell Coriolano is acknowledged by his peers and Thieme Publishers as the “heart and soul” of the IJSM as it exists today. The level of scientific quality and international recognition attained by the IJSM is in large part due to his valuable contributions and scientific rigor. It is therefore with great regret that we bid him farewell, but we are sure that his guidance and spirit will continue to shape the future of this publication.